Spherical echelon coated lithium manganese iron phosphate positive electrode material and preparation method and application thereof

Through spherical ladder coating technology, the poor conductivity and manganese ion dissolution of lithium manganese iron phosphate positive electrode material are solved, and the conductivity and cyclic stability of the material are significantly improved. It is suitable for high-energy-density power batteries.

CN119517971APending Publication Date: 2025-02-25SHANGHAI NAT ENG RES CENT FORNANOTECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771594.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The poor conductivity of lithium manganese iron phosphate positive electrode material and the problem of manganese ion dissolution lead to poor rate performance and cycle stability.

Method used

The preparation method of spherical ladder coating is adopted, and multiple ball mills and carbon coating treatments are used to form a multi-layer carbon coating structure to improve the conductivity and stability of the material.

Benefits of technology

The conductivity, rate performance and cycle stability of lithium manganese iron phosphate positive electrode material is significantly improved, and the battery-grade usage requirements are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a spherical echelon coated lithium manganese iron phosphate positive electrode material and a preparation method and application thereof, the chemical formula of lithium manganese iron phosphate is LiMn < 1-x > FexPO4, and the positive electrode material is obtained by spherical echelon coating. According to the obtained spherical echelon-coated lithium manganese iron phosphate positive electrode material, the electrical property of the lithium manganese iron phosphate positive electrode material is greatly improved, excellent rate performance, low-temperature performance and cycle performance are shown, the cost of raw materials and instruments is low, the production efficiency is high, and large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium-ion batteries, and specifically relates to a spherical step-coated lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, as an upgraded alternative material to lithium iron phosphate, lithium manganese iron phosphate (LMFP, LiMn 1-x Fe x PO4) has attracted much attention from the market. Lithium manganese iron phosphate is a high-voltage (4.1 V) phosphate material. It is doped with a certain amount of manganese on the basis of lithium iron phosphate, and the voltage platform of the material is increased by adjusting the manganese-iron ratio. It has similar properties to lithium iron phosphate and lithium manganese phosphate. Compared with lithium iron phosphate, lithium manganese iron phosphate has better thermal stability, chemical stability and economy, and also has higher energy density. Therefore, in recent years, researchers have extensively studied lithium manganese iron phosphate and believe that it is expected to become a new generation of high-energy density power battery positive electrode material. However, there are still some problems to be solved in the use of lithium manganese iron phosphate: 1) Due to the limitations of structural characteristics, its conductivity is poor and the lithium ion diffusion rate is low, which in turn affects the rate performance; 2) The Jahn-Teller effect promotes manganese precipitation, resulting in the attenuation of the material cycle life and reduced cycle stability. At present, the methods for improving the performance of lithium manganese iron phosphate materials mainly include material nano-sizing, carbon coating and ion doping. Material nano-sizing can make the material contact with the electrolyte more fully, shorten the lithium ion migration path, and thus improve the charge and discharge capacity and rate performance of the material. At the same time, the electrochemical properties of the material can also be improved by designing a special morphology. Carbon coating can effectively build a fast conductive network by evenly coating the surface of the material with carbon coating, providing a + Diffusion provides an effective channel to improve the conductivity of the material and inhibit the growth and agglomeration of crystal particles. By doping ions in the material, defects can be generated in the original lattice, making Li + The diffusion channel expands and the carrier density of the material increases, thereby improving the conductive properties of the material itself. Summary of the invention

[0003] The present invention aims to provide a spherical hierarchically coated lithium manganese iron phosphate positive electrode material to improve the current problems of low conductivity and dissolution of manganese ions in lithium manganese iron phosphate materials.

[0004] Another object of the present invention is to provide a method for preparing the above-mentioned spherical step-coated lithium manganese iron phosphate positive electrode material product.

[0005] Another object of the present invention is to provide an application of the above product.

[0006] The object of the present invention is achieved by the following scheme: a spherical hierarchically coated lithium manganese iron phosphate positive electrode material, wherein the chemical formula of lithium manganese iron phosphate is LiMn 1-x Fe x PO4, the positive electrode material is a spherical hierarchically coated positive electrode material.

[0007] The present invention provides a method for preparing a spherical hierarchically coated lithium manganese iron phosphate positive electrode material, comprising the following steps: Solid phase ball milling of initial raw materials: (1) mixing a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source and ethanol in a ball mill, wherein the raw materials of lithium iron manganese phosphate are mixed and ball milled at a molar ratio of lithium: manganese: iron: phosphorus of 1:0.6:0.4:1; (2) The raw materials after ball milling are dried, ground, and sintered at low temperature to obtain precursor 1; Secondary coating: (3) Transferring the precursor 1 and the carbon source to the planetary ball mill again for ball milling; (4) Drying, grinding, and sintering the ball-milled material to obtain precursor 2; Three times wrapping: (5) transferring the precursor 2 and the carbon source to a planetary ball mill for a third time for ball milling; (6) The ball-milled raw materials are prepared into a solution of a certain concentration, spray-dried, and sintered to obtain the desired positive electrode material.

[0008] The present invention obtains a primary carbon-coated ferromanganese phosphate precursor 1 through the first step, and then pulverizes the precursor 1 and performs carbon coating through the second step to obtain a double-coated precursor 2; after pulverizing the precursor 2 through the third step, three layers of coating are performed, and spheroidization treatment is performed, and sintering is performed to obtain a spherical echelon-coated positive electrode material. The method of the present invention ensures the consistency of the ferromanganese phosphate material and the uniformity of the coating, greatly improving the consistency of the product. At the same time, the spherical echelon phosphoric acid improves the conductivity of the material, greatly improves its rate performance and cycle performance, and meets the battery-level use requirements.

[0009] Furthermore, in step (1), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium sulfate; the manganese source is any one or two or more of manganese sulfate, manganese carbonate, and manganese tetraoxide; the iron source is any one or two or more of ferric phosphate, ferrous oxalate, and ferrous sulfate; the phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, ferric phosphate, and phosphoric acid; and the carbon source is one or two or more of glucose, sucrose, citric acid, graphene, carbon nanotubes, etc.

[0010] Furthermore, in step (1), the lithium source, manganese source, iron source and phosphorus source are mixed in a proportion, wherein the ratio of beads to material is 12:1.

[0011] Furthermore, in the solid phase ball milling preparation step, the drying temperature of the initial raw material is 50°C to 85°C, and the material is dried in a vacuum drying oven for 4 h to 12 h.

[0012] Furthermore, in step (2), the low-temperature sintering is carried out in a vacuum tube furnace, the sintering temperature is 200°C to 400°C, and the sintering time is 1 h to 3 h.

[0013] Furthermore, in step (4), the sintering temperature is 300°C to 550°C, and the sintering time in the vacuum tube furnace is 2 h to 5 h.

[0014] Furthermore, in step (6), spray drying is performed using a spray dryer with a feed rate of 5 mL / min to 25 mL / min, an inlet temperature of 180°C to 240°C, and an outlet temperature of 90°C to 140°C; the sintering temperature is 550°C to 700°C, and the sintering is performed in a vacuum tube furnace for 5 h to 8 h.

[0015] Furthermore, the planetary ball mill is set at a rotation speed of 200 r / min to 500 r / min, and the time is 6 h to 24 h.

[0016] The present invention also provides an application of spherical step-coated lithium manganese iron phosphate as a positive electrode material in a lithium battery.

[0017] The present invention adopts a spherical step-coating preparation method, which improves the electrical properties of lithium manganese iron phosphate positive electrode materials, improves the cycle performance and rate performance of lithium manganese iron phosphate, and has low raw material and instrument costs, high production efficiency, and can achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Comparison of the cycle performance of Example 1 and Comparative Example 1. After 300 cycles, the capacity retention rate of Example 1 is still 88.9%; Figure 2 Comparison of impedance performance between Example 1 and Comparative Example 1. The impedance of the battery assembled by spherical cascade coating in Example 1 is much smaller than that of the battery assembled by single coating in Comparative Example 1. Figure 3Example 1 shows the room temperature and low temperature rate performance diagram. Its 0.2C specific capacity is nearly 154.8 mA·h / g, its 10C specific capacity is 110.1 mA·h / g, and its 0.2C specific capacity is 150.7 mA·h / g, showing excellent rate performance. Under low temperature conditions, its 0.2C specific capacity is 126.6 mA·h / g, its 10C specific capacity is 85.4 mA·h / g, and its 0.1C specific capacity is 121.2 mA·h / g, showing excellent low temperature performance. DETAILED DESCRIPTION

[0019] In order to further explain the technical solution of the present invention, the present invention is described in detail with reference to specific implementation cases below.

[0020] Example 1 A spherical step-coated lithium manganese iron phosphate positive electrode material is obtained by spherical step-coating, and is prepared according to the following steps: Solid phase ball milling of initial raw materials: (1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 8 wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry. The mixture was ball milled for 12 hours at a rotation speed of 450 r / min. (2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was then taken out and transferred to a tube furnace and calcined at 350°C for 1.5 hours to obtain precursor 1. Secondary coating: (3) The precursor obtained in step (2) was transferred to a ball mill, 3 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, which was ball milled for 12 hours at a speed of 450 r / min; (4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dried powder was collected and transferred to a tube furnace and calcined at 450°C for 3 hours to obtain precursor 2. Three times coating (5) The obtained precursor 2 was transferred to a ball mill, 1 wt% glucose was added, and ethanol was added to perform ball milling for three times to obtain the coating slurry. The ball milling was performed for 8 hours at a speed of 450 r / min. (6) The ball-milled slurry was transferred to a spray dryer and spray granulated at a rate of 8 mL / min under the conditions of an inlet temperature of 200°C and an outlet temperature of 110°C. The collected dry powder was taken out and transferred to a tubular furnace for calcination at a temperature of 680°C for 8 hours to obtain a spherical hierarchically coated lithium manganese iron phosphate positive electrode material having a molecular formula of LiMn 0.4 Fe 0.6 PO4.

[0021] The first discharge specific capacity and low-temperature first discharge specific capacity of this embodiment are shown in Table 1.

[0022] Example 2 A spherical hierarchically coated lithium manganese iron phosphate positive electrode material is prepared according to the following steps: Solid phase ball milling of initial raw materials: 1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 8 wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry. The ball milling was performed for 6 hours at a rotation speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 350°C for 1.5 hours to obtain precursor 1. Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 1 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, which was ball milled for 12 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dried powder was collected and transferred to a tube furnace and calcined at 450°C for 3 hours to obtain precursor 2. Three times coating 5) Transfer the obtained precursor 2 to a ball mill, add 1wt% glucose, add ethanol and perform ball milling three times to obtain the coated slurry, and ball mill for 12 hours at a speed of 450 r / min; 6) The ball-milled slurry was transferred to a spray dryer, and spray granulation was performed at a rate of 8 mL / min under the conditions of an inlet temperature of 200°C and an outlet temperature of 110°C. The collected dry powder was taken out and transferred to a tube furnace for calcination at a temperature of 680°C for 8 hours to obtain a spherical hierarchically coated lithium manganese iron phosphate positive electrode material having a molecular formula of LiMn 0.4 Fe 0.6 PO4.

[0023] The first discharge specific capacity and low-temperature first discharge specific capacity of this embodiment are shown in Table 1.

[0024] Example 3 A sequentially coated lithium manganese iron phosphate positive electrode material is prepared according to the following steps: Solid phase ball milling of initial raw materials: 1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 8 wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry. The ball milling was performed for 6 hours at a rotation speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 350°C for 1.5 hours to obtain precursor 1. Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 5 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, which was ball milled for 18 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dried powder was collected and transferred to a tube furnace and calcined at 450°C for 3 hours to obtain precursor 2. Three times coating 5) The obtained precursor 2 was transferred to a ball mill, 1wt% glucose was added, and ethanol was added to perform ball milling three times to obtain the coated slurry, and the ball milling was performed for 8 hours at a speed of 450 r / min; 6) The ball-milled slurry was transferred to a spray dryer, and spray granulation was performed at a rate of 8 mL / min under the conditions of an inlet temperature of 200°C and an outlet temperature of 110°C. The collected dry powder was taken out and transferred to a tube furnace for calcination at a temperature of 680°C for 8 hours to obtain a spherical hierarchically coated lithium manganese iron phosphate positive electrode material having a molecular formula of LiMn 0.4 Fe 0.6 PO4.

[0025] The first discharge specific capacity and low-temperature first discharge specific capacity of this embodiment are shown in Table 1.

[0026] Comparative Example 1 Solid phase ball milling of initial raw materials: 1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 3wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry, and the ball milling was performed for 30 hours at a rotation speed of 450 r / min; 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and burned at 450°C for 3 hours to obtain precursor 1. Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 8 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, which was ball milled for 8 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to a spray dryer, and spray granulation was performed at a rate of 8 mL / min under the conditions of an inlet temperature of 200°C and an outlet temperature of 110°C. The collected dry powder was taken out and transferred to a tube furnace for calcination at a calcination temperature of 680°C for 6.5 hours to obtain a secondary coated spherical hierarchically coated lithium manganese iron phosphate positive electrode material, the molecular formula of which is LiMn 0.4 Fe 0.6 PO4.

[0027] The first discharge specific capacity and low-temperature first discharge specific capacity of this comparative example are shown in Table 1.

[0028] Comparative Example 2 Solid phase ball milling of initial raw materials: 1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 8 wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry. The ball milling was performed for 12 hours at a rotation speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 680°C for 6.5 hours to obtain a primary coated spherical lithium manganese iron phosphate positive electrode material. The molecular formula of the lithium manganese iron phosphate positive electrode material is LiMn 0.4 Fe 0.6 PO4.

[0029] The first discharge specific capacity and low-temperature first discharge specific capacity of this comparative example are shown in Table 1.

[0030] Comparative Example 3 Solid phase ball milling of initial raw materials: 1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 15wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry. The ball milling was performed for 12 hours at a rotation speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven, and then to a spray dryer. The spray granulation was performed at a rate of 8 mL / min under the conditions of an inlet temperature of 200°C and an outlet temperature of 110°C. The collected dry powder was taken out and transferred to a tube furnace for calcination at a calcination temperature of 680°C for 6.5 hours to obtain a once-coated spherical lithium manganese iron phosphate positive electrode material. The molecular formula of the lithium manganese iron phosphate positive electrode material is LiMn 0.4 Fe 0.6 PO4. The only difference between Comparative Example 3 and Comparative Example 2 is the amount of glucose added.

[0031] The first discharge specific capacity and low-temperature first discharge specific capacity of this comparative example are shown in Table 1.

[0032] Electrochemical properties of lithium manganese iron phosphate cathode material: The electrochemical properties of the active material lithium manganese iron phosphate positive electrode material prepared in the examples and comparative examples were tested, and the specific method is as follows: The tests were conducted based on CR2032 button cells, using lithium metal sheets as counter electrodes, PE / PP as separators, and LiPF6 as electrolyte; follow the steps below: (1) The active material, the conductive agent and polyvinylidene fluoride (PVDF) were mixed and ground in a mass ratio of 8:1:1, and N-methyl-2-pyrrolidone (NMP) was used as a solvent; (2) coating the slurry after grinding in step (1) on aluminum foil using a preparation device to control the thickness to 200 μm, and then transferring it to a vacuum oven at 120° C. and drying it for 12 h; (3) The electrodes were cut into small discs with a diameter of 12 mm and transferred to a glove box filled with argon gas to be assembled into button cells.

[0033] Impedance performance test method: Under normal temperature, the battery disturbance voltage is 5mV, and the scanning frequency is 0.1-100kHz; Cycle performance test method: Under normal temperature, the battery is charged to 4.5V at a current density of 0.2C, then switched to 4.5V constant voltage charging. When the charging current is less than 0.05C, the charging is cut off; let it stand for 10 minutes, then discharge to 2.8V at a current density of 0.2C; let it stand for 10 minutes. Repeat the above steps to complete 300 cycles.

[0034] Table 1 Examples and Comparative Examples Normal and Low Temperature Discharge Specific Capacity: As shown in Table 1, the lithium-ion battery prepared by the nano-manganese iron lithium phosphate obtained in the present invention exhibits good electrochemical performance. Among them, the lithium-ion battery prepared by the nano-manganese iron lithium phosphate obtained in Example 1 has a room temperature first discharge specific capacity of 154.8 mAh g -1 The low-temperature first discharge capacity is 126.6 mAh g -1 .like Figure 1 The capacity retention rate of Example 1 after 300 cycles is still 88.9%. Figure 2 As shown in the figure, the impedance comparison between Example 1 and Comparative Example 1 shows that the impedance of the battery assembled by spherical cascade coating in Example 1 is much smaller than that of the battery assembled by single coating. Figure 3 As shown in the room temperature and low temperature rate performance diagram of Example 1, it is known that its 0.2C specific capacity is nearly 154.8 mA·h / g, the 10C specific capacity is 110.1 mA·h / g, and the 0.2C specific capacity is 150.7 mA·h / g, showing excellent rate performance; under low temperature conditions, its 0.2C specific capacity is 126.6 mA·h / g, the 10C specific capacity is 85.4 mA·h / g, and the 0.1C specific capacity is 121.2 mA·h / g, showing excellent low temperature performance.

[0035] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A spherical hierarchically coated lithium manganese iron phosphate positive electrode material, characterized in that: The chemical formula of the lithium iron manganese phosphate is LiMn 1-x Fe x PO4, the lithium manganese iron phosphate positive electrode material is obtained by spherical step-by-step coating.

2. A method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material as claimed in claim 1, characterized in that: The method is obtained by solid phase ball milling of the initial raw material, secondary coating and tertiary coating, including the following steps: Solid phase ball milling of initial raw materials: (1) mixing a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source and ethanol in a ball mill, wherein the raw materials of lithium iron manganese phosphate are mixed and ball milled at a molar ratio of lithium: manganese: iron: phosphorus of 1:0.6:0.4:1; (2) The raw materials after ball milling are dried, ground, and sintered at low temperature to obtain precursor 1; Secondary coating: (3) Transferring the precursor 1 and the carbon source to the planetary ball mill again for ball milling; (4) Drying, grinding, and sintering the ball-milled material to obtain precursor 2; Three times wrapping: (5) transferring the precursor 2 and the carbon source to a planetary ball mill for a third time for ball milling; (6) The ball-milled raw materials are prepared into a solution of a certain concentration, spray-dried, and sintered to obtain a spherical hierarchically coated lithium manganese iron phosphate positive electrode material.

3. The method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step (1), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium sulfate; the manganese source is any one or two or more of manganese sulfate, manganese carbonate, and manganese tetraoxide; the iron source is any one or two or more of ferric phosphate, ferrous oxalate, and ferrous sulfate; the phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, ferric phosphate, and phosphoric acid; the carbon source is one or two or more of glucose, sucrose, citric acid, graphene, carbon nanotubes, etc.

4. The method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In the preparation step (2), the drying temperature is 50°C to 85°C, and the drying is carried out in a vacuum drying oven for 4 h to 12 h.

5. The method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step (2), the sintering temperature is 200°C to 400°C, and the sintering time is 1 h to 3 h in a vacuum tube furnace.

6. The method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step (4), the sintering temperature is 300°C to 550°C, and the sintering time is 2 h to 5 h in a vacuum tube furnace.

7. The method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step (6), spray drying is performed using a spray dryer with a feed rate of 5 mL / min to 25 mL / min, an inlet temperature of 180°C to 240°C, and an outlet temperature of 90°C to 140°C; the sintering temperature is 550°C to 700°C, and the sintering is performed in a vacuum tube furnace for 5 h to 8 h.

8. The method for preparing the spherical hierarchically coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: The speed of the planetary ball mill is set to 200 r / min ~ 500 r / min, and the ball milling time is 6 h ~ 24 h.

9. Use of the spherical hierarchically coated lithium manganese iron phosphate according to claim 1 as a positive electrode material in a lithium battery.